Occurrence and Spatial Distribution of Antibiotic-Resistant Bacteria and Antibiotic Resistance Genes in Surface and Groundwater of the Kelani River Basin, Sri Lanka - Meddage Anjana Kelum Mithurangana M Kumara; Gayani Yasodara Liyanage; Fathima Sumaiya Idroos; Jayakodi Achchige Ganguli Vimansa Sewmi; Weiping Liu; Shanshan Yin; Rohan Goonetilleke; Rohitha Bandara; Lakmal Diyawaththege; Pathmalal Marakkale Manage (Current Microbiology, 2026)

Impact of compost application on the spread of antibiotic resistance: emerging risks to public and aquatic health in Sri Lanka - J. A. G. V. Sewmi; G. Y. Liyanage; P. A. K. C. Wijerathna; Weiping Liu; Shanshan Yin; Pathmalal M. Manage (Environmental Geochemistry and Health, 2026)

Environmental surveillance of antibiotic-resistant Escherichia coli in Sri Lankan inland waters: Detection of resistance genes and Shiga toxin–producing strains - Meddage Anjana Kelum Mithurangana M Kumara; Gayani Yasodara Liyanage; Pavithrani Sadupama Manage; Pathmalal Marakkale Manage (Environmental Monitoring and Assessment, 2026)

Different Extraction Procedures and Assessment of Proteins from Five Sri Lankan Seaweed Species - Jayani Samarathunga; Isuru Wijesekara; Madhura Jayasinghe; M. M. Pathmalal (Journal of Aquatic Food Product Technology, 2025)

Suspended sediment (SPS) triggers nitrogen retention by altering microbial network stability and electron transport behavior during the aerobic-anoxic transition - Xiaoyan Liu; Tingting Pei; Guojia Xu; Tinglin Huang; Yaoguo Wu; Xiaowei Jin; Yi Cao; Ran Sun; Sihai Hu; Pathmalal M. Manage; Xiang Liu; Tao Liu; et al. (Journal of Environmental Management, 2025)

An analysis of regional variations in the physicochemical properties of Cocos nucifera L. var. nana across Sri Lanka - Dayani Pavalakumar; Lanka Jeewanie Samarakoon Undugoda; Kasun Madhusanka Thambugala; Pathmalal Marakkale Manage; Ruwani Nilushi Nugara; Sagarika Dilpushpi Kannangara; Suranga M. Rajapaksha (Plant Physiology Reports, 2024)

Spatial and temporal variation of physicochemical parameters of coastal waters in the southwestern region of Sri Lanka - J. K. P. C. Jayawardhane; K. A. W. S. Weerasekara; M. M. Pathmalal (Sri Lanka Journal of Aquatic Sciences, 2023)
Physicochemical parameters of coastal water in the southwestern area of Sri Lanka were studied from January to November 2016. Surface water samples from 15 selected locations were analysed according to standard methods. The ranges of the values recorded were; water temperature (WT) 26.5-33.9 ºC, pH 7.1-8.4, dissolved oxygen (DO) 4.4-7.4 mg L-1, salinity 14-38 ppt, electrical conductivity (EC) 27.1-53.8 mS cm-1, total suspended solids (TSS) 50.2-403.4 mg L-1, turbidity 1.2-64.9 NTU, nitrate nitrogen (NO3--N) 0.00-0.57mg L-1, nitrite nitrogen (NO2--N) 0.00-0.035mg L-1, ammoniacal nitrogen (NH4+-N) 0.00-1.72mg L-1, dissolved inorganic phosphorous (DIP) 0.00-0.65 mg L-1, biochemical oxygen demand (BOD) 0.1-11.6 mg L-1 and chemical oxygen demand (COD) 40-768 mg L-1. Results of Two-way ANOVA showed that there was a seasonal variability in parameters such as water temperature (p

Permeable Reactive Barriers as an In Situ Groundwater Remediation Technique for Open Solid Waste Dumpsites: a Review and Prospect - R. B. C. D. Jayasundara; K. P. P. Udayagee; A. K. Karunarathna; Pathmalal M. Manage; Ruwani N. Nugara; K. M. R. D. Abhayapala (Water, Air, & Soil Pollution, 2023)

Nutritional Value and Potential Applications of Jellyfish - R. A. S. N. Ranasinghe; W. L. I. Wijesekara; P. R. D. Perera; S. A. Senanayake; M. M. Pathmalal; R. A. U. J. Marapana (Journal of Aquatic Food Product Technology, 2022)

Prevalence and Quantitative Analysis of Antibiotic Resistance Genes (ARGs) in Surface and Groundwater in Meandering Part of the Kelani River Basin in Sri Lanka - G. Y. Liyanage; A. Illango; Pathmalal M. Manage (Water, Air, & Soil Pollution, 2021)

Retirement of a distinguished researcher - Prof. Upali S. Amarasinghe - M. M. Pathmalal (Sri Lanka Journal of Aquatic Sciences, 2021)
No abstract available

Cyanotoxins: A hidden cause of Chronic Kidney Disease of unknown etiology (CKDu) in Sri Lanka - A review - Pathmalal M Manage (Sri Lanka Journal of Aquatic Sciences, 2019)
CKDu has been identified as a major public health issue in countries such as Sri Lanka, India and Nicaragua, which causes significant deaths per year. Significant similarities have been observed among these endemic nephropathies regardless of their geographical separation. Existing evidence favors a multi-factorial etiology, but research over the last few decades has failed to recognize the specific risk factors. Based on the geographical distribution that is unique and evidence of histopathological nature, it is speculated that CKDu is environmentally induced health problem. Hypothesis linking acetylcholinesterase (AChE) inhibiting organophosphate pesticides, metal-chelating glyophosate, agrochemicals, cadmium, arsenic, fluoride, hardness, and algae/cyanobacteria are considered as important factors in the etiology of CKDu. However, to date, no single geochemical parameter is shown to be directly related to the CKD etiology on the basis of the elements determined during research studies, and it is very likely that the unique hydrogeochemistry and microbiology of the drinking water is closely associated with the incidence of the disease in the endemic areas. The paper discuss understudied area of research is whether cyanotoxin formation from algal blooms may be a risk factor that contributes to CKDu in Sri Lanka as cyanotoxins in CKDu has been considered but not investigated.

Heavy metal contamination status in seven fish species from reservoirs of Polonnaruwa district, Sri Lanka - Hiran Wijesinghe; F. Sumaiya Idroos; Pathmalal M. Manage (Sri Lanka Journal of Aquatic Sciences, 2018)
Heavy metal contamination in aquatic ecosystems has become an emerging environmental issue. The stable physico-chemical properties of heavy metals could result in bioconcentration and bioaccumulation in different organs of freshwater fishes. The present study records the accumulation of Lead (Pb), Cadmium (Cd), Chromium (Cr), Copper (Cu) and Zinc (Zn) in the head, muscle and skin regions of seven fish species namely, Labeo rohita, Oreochromis mossambicus, Oreochromis niloticus, Etroplus suratensis, Heteropneustes fossilis, Oligolepsis acutipennis and Puntius dorsalis collected from Minnerya, Parakrama Samudraya and Kaudulla reservoirs in Polonnaruwa district, Sri Lanka. The results showed that both Pb and Cd accumulated in high concentrations in the head region compared to the skin and muscles of the fish samples. The highest amounts of Pb (22.44±5.48 mg/Kg) and Cd (4.98±0.86mg/Kg) were recorded from the head parts of the H. fossilis in Minneriya and O. niloticus in Kaudulla respectively, whereas the highest amount of Cr (30.87±4.51mg/Kg) was detected in head part of the O. acutipennis in Minneriya. The Cu concentration was the highest (2.92±0.001 mg/Kg) in head regions of H. fossilis from Minneriya. Zn was the most abundant heavy metal detected in the head, muscle and skin regions of fish in all three reservoirs. The highest amount of Zn (118.93±10.55mg/Kg) was detected in the head part of O. acutipennis from Minneriya. The Pb, Cd, Cr, Cu and Zn concentrations detected in the head part of popular edible freshwater species, O. mossambicus, O. niloticus and E. suratensis were higher than the provisional tolerable weekly intake (PTWI) of Pb (0.025 mg/Kg), Cd (0.007 mg/Kg), Cr (0.1 mg/Kg), Cu (3.5 mg/Kg) and Zn (7 mg/Kg) specified by the FAO/WHO. Therefore, long-term consumption of these fish species especially the head parts may lead to accumulation of these heavy metals in tissues and lead to chronic diseases which may risk the health of consumers especially in the north-central province of Sri Lanka.

Heavy use of antibiotics in aquaculture: Emerging human and animal health problems – A review - Pathmalal M. Manage (Sri Lanka Journal of Aquatic Sciences, 2018)
Antibiotics have been extensively and effectively used in aquaculture due to accelerated growth of aquaculture and this has resulted in the development of serious health problems in aquaculture, other animals, and human. The use of a wide variety of antibiotics in large amounts, including non-biodegradable antibiotics, ensures that they remain in the aquatic environment for a long time. This has resulted; the emergence of antibiotic-resistant bacteria in the environments, an increase of antibiotic resistance in fish pathogens, transfer of these resistance determinants to bacteria and then land animals and finally become human pathogens along with alterations of the bacterial ﬂora both in sediments and in the water column. Thus, the global efforts are needed to promote more judicious use of prophylactic antibiotics in aquaculture as accumulating evidence indicates that unrestricted use is detrimental to fish, terrestrial animals and human health.

Trophic coupling of a testate amoeba and Microcystis species in a hypertrophic pond - Yuichiro Nishibe; Pathmalal M. Manage; Zen?ichiro Kawabata; Shin-ichi Nakano (Limnology, 2004)

Seasonal changes in densities of cyanophage infectious to Microcystis aeruginosa in a hypereutrophic pond - Pathmalal. M. Manage; Zen'ichiro Kawabata; Shin-ichi Nakano (Hydrobiologia, 1999)